Efficacy of olfactory training program in conjunction with nasal steroid irrigation in treating persistent smell loss in COVID-19 patients - Marwa Abdelhafeez; Safaa Mostafa Ali Elkholi (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2022)
Background: Smell loss is a challenging clinical problem. There is still no evidence-based medical intervention to treat patients with persistent smell loss as a result of Coronavirus Disease 2019 (COVID-19). The aim is to analyze the efficacy of treating patients with persistent smell loss due to COVID-19 using olfactory training (OT) combined with nasal steroid irrigation.  Methods: A cross-sectional study enrolled 196 COVID-19 patients with persistent smell loss were recruited. All patients underwent two testing sessions. At the first session, patients were examined by a history taking followed by an Otorhinolaryngological examination including, a thorough nasal endoscopy. In addition, an olfactory performance assessment was performed to assess the severity of smell loss. All patients were then treated with OT and nasal steroid irrigation with budesonide for 12 weeks. The second session includes an olfactory performance assessment to assess if there is an improvement in olfactory function.  Results: Patients after treatment showed improvement in overall Threshold-Detection-Identification (TDI) score, odor detection threshold score, odor discrimination score, and odor identification score, which were higher than before treatment. Statistically significant differences before and after treatment results were very pronounced for the overall TDI score (p = 0.014) and odor detection threshold score (p = 0.003). There was no significant difference in odor discrimination (p = 0.08) or odor identification (p = 0.126) scores before and after treatment.  Conclusion: The results of this study support the efficacy of the combination of budesonide nasal irrigation and OT in treating persistent smell loss due to COVID-19 infection.